Dynamic structural analysis of ramming in bighorn sheep - Drake, Aaron Michael, author; Haut Donahue, Tammy L., advisor; Donahue, Seth W., advisor; Stansloski, Mitchell, committee member; Heyliger, Paul, committee member (Colorado State University. Libraries, 2015)
Concussions are the most common traumatic brain injury and are caused by impulsive loads applied to the skull, resulting in relative motion of the brain within the brain cavity. Despite wearing helmets, athletes involved in full contact sports, such as football, are highly susceptible to concussive injuries. Short term symptoms of concussions include nausea, headache and confusion and there is evidence of more serious, long term effects from repeated concussions. Furthermore, the physical mechanisms of concussions are not well understood, making them difficult to diagnose and treat clinically. Male bighorn sheep sustain massive impact loads to the head during ramming, which is done as a means of determining hierarchy and gaining mating privileges. These large animals thrust themselves, horns first, at one another and collide violently, repeating this ritual for up to several hours until the subdominant male succumbs. After a collision, the animals are stunned momentarily but otherwise appear to suffer no ill effects, based on behavioral observations. This simple fact provided the motivation to examine the dynamic structural behavior of bighorn sheep horns and skulls. For reference, the average translational brain cavity accelerations observed during finite element model impact were found to be 111g (1091 m/s²) and impacts thought to be damaging to human brains occur at around 100g. A dynamic finite element impact model was produced using the geometry, obtained from a CT scan, of a mature male bighorn sheep’s skull and horns. Quantitative and qualitative results of the simulation were examined to determine mechanisms of energy dissipation and stress distribution during an idealized impact event. Video analysis of particularly forceful ramming sequences of wild bighorn sheep was carried out to estimate the dynamics involved with ramming. In order to investigate the relative contributions of the horn curl as well as the internal foamy bone architecture, three separate finite element models were produced. One model had one half of the horn length removed, another had the internal foam-like bone removed and these models were compared to the fully intact model to determine the structural contributions of these features during impact. Removing one half of the horn curl had the effect of increasing the peak brain cavity translational acceleration by 49%. Eliminating the internal foamy bone architecture resulted in a dramatic 442% increase in brain cavity rotational accelerations. The dynamic (vibrational) response of bighorn sheep horns and skulls was investigated using two, related methods: finite element modal analysis and experimental modal analysis. The finite element modal analysis revealed five dominant natural frequencies with values ranging from 118 to 309 Hz. Experimental modal analysis revealed several natural frequencies between 100 and 300 Hz, however, differentiating specific modes was difficult. For both vibrational analyses the dominant vibrational mode shape was side-to-side oscillations of the horn tip. This study hopes to promote and guide further research on the mechanisms of brain trauma prevention in bighorn sheep, with an emphasis on the structural and material characteristics of the horn and skull, to increase our understanding of, and ways to prevent traumatic brain injuries in humans.
Keywords: bighorn sheep; concussions; finite element analysis; impact; ramming; vibration